A presentation of the socially responsible region of Northern of Cauca - Azuero Rodríguez, Andrés; Melo, Jenny Marcela; García, Mónica (Cuadernos de Administración, 2011)
Socially Responsible Territories as spatial strategy of Corporate Social Responsibility (CSR) are being developed in different parts of Colombia. In the case of Northern Cauca Region emerges as an initiative of entrepreneurs with the aim of responding to local needs and bet on the construction of a process of social intervention in the framework of a regional development agenda, including the prospect of multiple actors and entrepreneurs settled zones in the area, local governments, academia and representatives of the community. This reflection article aims to describe the process of collective construction of the Socially Responsible Territory of Northern Cauca. It comes in three parts: the first describes the main conceptual references about Corporate Social Responsibility and Socially Responsible Region. The second part outlines the main features of the area of northern Cauca and the context of implementing the strategy. In the last part presents the strategy Socially Responsible Region in Northern Cauca, the milestones of the process of coordination of actors that has allowed the formation of the strategy and present some preliminary thoughts and findings on the learning achieved at this stage of the process.